DETERMINAN HARGA SAHAM PERUSAHAAN MANUFAKTUR SUBSEKTOR FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Amyati, Amyati; Nopiandri, Nopiandri (LPPM Universitas Bina Bangsa, 2023)
In 2020 the growth of the Chemical, Pharmaceutical and Traditional Medicine Industry group reached 9.39%, which was not only an increase but also the highest growth in the industrial group among other industrial groups. has caused the pharmaceutical industry to be included in a strategic industry which resulted in the price of pharmaceutical stocks increasing during the Covid-19 pandemic. The purpose of this study was to determine the effect of BVPS, TATO, FZ, EPS, and PER on stock prices in pharmaceutical sub-sector companies 2017-2021. The method used in this research is quantitative. The results showed that partially BVPS and TATO variables had an effect on stock prices, while FZ, EPS, and PER had no effect on stock prices. Simultaneously BVPS, TATO, FZ, EPS, and PER affect stock prices